University Management Information System (UMIS) acceptance among university student: Applying the Extended Technology Acceptance Model (ETAM) - Raman, Arumugam (Macrothink Institute, 2011)
This study uses Extended Technology Acceptance Model (ETAM) to predict University Management Information System (UMIS) acceptance amongst postgraduate students.A model for UMIS acceptance is used to examine how various factors (technical support, and computer literacy) modified from Technology Acceptance Model (TAM) influence acceptance and its antecedents.This model is examined through an empirical study using structural equation modeling techniques.Results shows that perceived usefulness, perceived ease to use, technical support, and computer literacy were significant determinants of postgraduate students’ UMIS acceptance.The current research found that a strong positive relationships between the technical support and the usage of IU (UMIS).